2015
DOI: 10.3923/ijbc.2015.198.206
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Anti-Plasmodial Activity of Aqueous and Ethanolic Extracts of Moringa oleifera and Phyllanthus amarus

Abstract: Many herbal medicinal products contribute to the treatment of malaria in endemic areas. In Ghana, there is documented evidence of the use of several plant species in the management of both infectious and non-infectious diseases. This study sought to validate the activity of extracts from two such plants, Phyllanthus amarus and Moringa oleifera, against Plasmodium falciparum. Anti-plasmodial activities of aqueous and ethanolic extracts of M. oleifera (whole plant and twig) and P. amarus (whole plant and stem) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
5
2
Order By: Relevance
“…The in vitro antiplasmodial activity of P. amarus had similarly been reported by Donkor et al . [ 21 ] who reported antimalarial activity of 80.09% at 100 μg/ml which is comparatively higher than what we obtained (76.8% at 100 μg/ml). The findings of this work also agree with Uchenna et al .…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The in vitro antiplasmodial activity of P. amarus had similarly been reported by Donkor et al . [ 21 ] who reported antimalarial activity of 80.09% at 100 μg/ml which is comparatively higher than what we obtained (76.8% at 100 μg/ml). The findings of this work also agree with Uchenna et al .…”
Section: Discussioncontrasting
confidence: 84%
“…The films were fixed in methanol, stained for 10 min in 10% Giemsa, and viewed under a light microscope after washing and drying. The percentage of parasite inhibition was calculated using the following formula:[ 21 ]…”
Section: Methodsmentioning
confidence: 99%
“…The possible mechanisms for which the biological activities observed in the leaf extract of M. oleifera, in this study, might likely be attributed to; antioxidant effect of the extract (Vergara-Jimenez et al, 2017), free radical scavenging property (Somsak et al, 2016), inhibition of protein synthesis or by other mechanism not known/reported in the literature. Although, the antiplasmodial activities of each solvent extracts reported in here are dependent on concentration, Donkor et al (2015) reported the contrary. In their work, inhibition of parasite growth by the extracts was observed to increase as the concentration of extracts decreased.…”
Section: Resultscontrasting
confidence: 62%
“…Seeding: For in vitro antimalarial activity assay, rings and trophozoites stages of synchronized P. falciparum culture (1% parasitaemia, 2% hematocrit) were used. Into duplicate wells of a sterile 96 wells flat bottom plate, an aliquot (180 µL) of sychronized culutre was added, following which, 20 µL of various concentrations (500, 250, 125, 62.5 µg/ml) respectively of crude plant extracts was added to columns 1-8 to yield a final concentration (50, 25, 12.5 and 6.25µg/mL) of each extract in the respective wells (Donkor et al, 2015). Columns 9 and 10 received 20 µL of the culture medium to serve as negative controls, while columns 11 and 12 received 20 µL different concentration (1000, 500, 250, 125, 62.50, 31.25 and 15.625 nM/mL) of chloroquine diphosphate (CQdiPO 4 ; Sigma aldrich) to serve as positive control.…”
Section: Parasite Culturementioning
confidence: 99%
“…Chuka Trin Cleanser, with M. oleifera and water as the sole constituents and having % parasitaemia reduction of 50.5%, and 67.3% on days 4 and 7 post treatment, may show that M. oleifera has appreciable antiplasmodial property. Other researchers (19,22,45) have also proved the antimalarial property of the plant. This investigation has demonstrated that the Deep root and Ruzu bitters herbal formulations have very strong inhibitory effect against P. berghei in M. musculus.…”
Section: Discussionmentioning
confidence: 96%